The Relation between Hepatotoxicity and the Total Coumarin Intake from Traditional Japanese Medicines Containing Cinnamon Bark - Iwata, Naohiro; Kainuma, Mosaburo; Kobayashi, Daisuke; Kubota, Toshio; Sugawara, Naoko; Uchida, Aiko; Ozono, Sahoko; Yamamuro, Yuki; Furusyo, Norihiro; Ueda, Koso; Tahara, Eiichi; Shimazoe, Takao (Frontiers in Pharmacology, 2016)
Cinnamon bark is commonly used in traditional Japanese herbal medicines (Kampo medicines). The coumarin contained in cinnamon is known to be hepatotoxic, and a tolerable daily intake (TDI) of 0.1 mg/kg/day, has been quantified and used in Europe to insure safety. Risk assessments for hepatotoxicity by the cinnamon contained in foods have been reported. However, no such assessment of cinnamon bark has been reported and the coumarin content of Kampo medicines derived from cinnamon bark is not yet known. To assess the risk for hepatotoxicity by Kampo medicines, we evaluated the daily coumarin intake of patients who were prescribed Kampo medicines and investigated the relation between hepatotoxicity and the coumarin intake. The clinical data of 129 outpatients (18 male and 111 female, median age 58 years) who had been prescribed keishibukuryogankayokuinin (TJ-125) between April 2008 and March 2013 was retrospectively investigated. Concurrent Kampo medicines and liver function were also surveyed. In addition to TJ-125, the patients took some of the other 32 Kampo preparations and 22 decoctions that include cinnamon bark. The coumarin content of these Kampo medicines was determined by high performance liquid chromatography (HPLC). TJ-125 had the highest daily content of coumarin (5.63 mg/day), calculated from the daily cinnamon bark dosage reported in the information leaflet inserted in each package of Kampo medicine. The coumarin content in 1g cinnamon bark decoction was 3.0 mg. The daily coumarin intake of the patients was 0.113 (0.049 - 0.541) mg/kg/day, with 98 patients (76.0%) exceeding the TDI. Twenty-three patients had an abnormal change in liver function test value, but no significant difference was found in the incidence of abnormal change between the group consuming less than the TDI value (6/31, 19.4%) and the group consuming equal to or greater than the TDI value (17/98, 17.3%). In addition, no abnormal change related to cinnamon bark was found for individual patients. This paper was done to assess the risk of hepatotoxicity by the coumarin contained in Kampo medicines and to clarify whether or not the Kampo preparations in general use that contain cinnamon bark may be safely used in clinical practice.